The Influence Of Using The Problem Solving Model And Teacher-Made Hots-Based Evaluation Questions On Student Learning Outcomes - Kirani, Nadila; Nasution, Toni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to find out the effect of using problem solving models and hots-based evaluation questions made by teachers on the learning outcomes of Al-Hijrah IT Middle School students. The type of research used is quantitative experiment using a quasi-experimental method. The population in this research is all grade students. IPS Vlll at Al-Hijrah IT Middle School for the 2024/2025 academic year. Namely 60 students consisting of social studies classes Vlll-1, Vlll-2, Vlll-3, the sampling technique used in this research is saturated sampling where the entire population is sampled, the data analysis technique used in this research is the multiple regression model , the results of this research are that in this research the use of problem solving methods has a significant influence on learning outcomes because the calculated t value t table (2.838 2.010) and the significance level is 0.007 0.05. In this research, teacher-made hot-based evaluation questions have a significant influence on learning outcomes because the calculated t value is t table (5.689 2.010) and the significance level is 0.000 0.05. In this study, the calculated f value was 74.111 and the significance level was 0.000. This shows that simultaneously the teacher-made hot-based evaluation questions and the use of problem solving methods had a significant effect on Critical Thinking Ability because the calculated f value f table (74.111 3.19) and significance level of 0.000 0.05